Management of Skeletal Class II Malocclusion in a Growing Patient Using Clear Aligners and Class II Elastics: A Case Report - Francesca Gazzani; Chiara Pavoni; Francesca Chiara De Razza; Letizia Lugli; Paola Cozza; Roberta Lione (Dentistry Journal, 2026)
Objective: Class II malocclusion with mandibular retrusion in growing patients is traditionally managed with functional appliances. Recent advances in clear aligner therapy have introduced new biomechanical approaches combining aligners with intermaxillary elastics. This case report describes the correction of a skeletal Class II malocclusion using clear aligners combined with Class II elastics during the pubertal growth spurt. Methods: An 11-year-old female patient with skeletal Class II due to mandibular retrusion, increased overjet, deep bite, and dental Class II relationship was treated with clear aligners, transverse expansion, bite ramps, attachments, and full-time Class II elastics. Results: After 24 months of treatment, favorable dentoskeletal and occlusal outcomes were achieved, including improvement of the sagittal relationship (ANB reduction from 7° to 4°), mandibular advancement (SNB increase from 76° to 79°), and correction of overjet and overbite. Conclusions: The combination of clear aligners and Class II elastics may represent a valid treatment option for growing patients with mandibular Class II malocclusion, providing effective sagittal correction and good control of dental movements when applied during the appropriate growth phase.